2004
DOI: 10.1039/b403988b
|View full text |Cite
|
Sign up to set email alerts
|

Solvent free synthesis of polyaniline–clay nanocomposites from mechanochemically intercalated anilinium fluoride

Abstract: Nanocomposites consisting of conducting polyaniline and clay minerals were successfully synthesized from mechanochemically intercalated anilinium fluoride; the nanocomposites prepared by the mechanochemical intercalation method contained much more polyaniline in the clay layers than those prepared by a conventional solution method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…As a result, the basal spacing of monomer-absorbed MMT changed from 1.58 to 1.42 nm. They are in the agreement with another publication [15]. …”
Section: Electrochemical Investigationsupporting
confidence: 81%
“…As a result, the basal spacing of monomer-absorbed MMT changed from 1.58 to 1.42 nm. They are in the agreement with another publication [15]. …”
Section: Electrochemical Investigationsupporting
confidence: 81%
“…As a result, the the basal spacing of monomer-absorbed MMT changed from 1.58 nm to 1.42 nm (2θ = 6.0°). They are in the agreement with other publications [54]. Figure 22 presents the Raman spectrum of PPy/MMT nanocomposite measured at 514 nm with 1 mW laser power.…”
Section: Xrd Patternssupporting
confidence: 79%
“…Huang and Kanner reported the synthesis of PANI nanofibers by phase transfer polymerization [9,10]. Furthermore, PANI was synthesized into the channels of inorganic hosts [11][12][13], generally, by absorbing the monomer in the host and then adding the oxidant. Among these, the host most commonly used for polymer nanocomposites are expandable-layered silicates, being maghnite (Magh, a natural sodium montmorillonite clay obtained from Tlemcen (Algeria)) a typical example.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the interlayer spacing can be modified, depending on the cation intercalated. Taking profit of the swelling of the montmorillonite when it is immersed in water, that produces a remarkable increase of the interlayer spacing [24], Yoshimoto et al explored the mechanochemical intercalation of different anilinium salts (chloride, fluoride and sulphate) into sodium montmorillonite layers prior to the polymerization [12,13,19]. They concluded that nanocomposites made using a solvent-free mechanochemical method, produced much more polyaniline between the montmorillonite layers than that obtained by conventional solution methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation